Parameter calibration method of clustered-particle logic concrete DEM model using BP neural network-particle swarm optimisation algorithm (BP-PSO) inversion method - Pan, Xupeng; Niu, Yanwei; Zhao, Yu; Huang, Pingming; Wu, Yizhen (Engineering fracture mechanics, 2023)
•A high precision microparameters calibration method is proposed for DEM model.•The initial damage, uniaxial compressive to tensile strength ratio and failure mode are firstly considered as calibration targets.•The MIV algorithm was used to quantify the impact level of each microparameter.•The concrete failure mechanism is investigated by mesoscale model using clustered-particle logic. A high precision back propagation neural network-particle swarm optimization (BP-PSO) algorithm inversion method is proposed to calibrate the microparameters of the clustered-particle logic concrete discrete element method model. The calibration targets include initial damage, failure mode, and mechanical properties of the material. The research utilise 243 training datasets generated through orthogonal experimental design and conducted simulations to train the BP neural network. In addition, a parameter sensitivity analysis is employed on the trained BP neural network to quantify the impact level of each microparameter and guide future macroparameter fine-tuning. The results indicate that the mean absolute percentage error of the BP-PSO inversion method is only 3.79%. This research also study on the concrete failure mechanism by using a mesoscale model based on clustered-particle logic, which considered concrete as a three-phase composite composed of mortar matrix, aggregates, and interfacial transition zone. The crack initiation, propagation and coalescence of DEM model show a good agreement with the experimental results.